Refleksi Mendalam Tentang Eksistensi Manusia Dalam Dunia: " Konflik Antara Israel Dan Palestina" - Tamara Wita Batubara; Yisefta Yohana Samosir; Tia Devita Manik; Junjungan Simoramgkir (Jurnal Pendidikan Agama dan Teologi, 2024)
In this research, the literary detective method is used to explore the ongoing conflict between Israel and Palestine. Through a library research approach, this article presents an in-depth study of human existence in the context of this conflict. The research results discuss the roots of the conflict that began with Israel's declaration in 1948, revealing the growing tension between Jewish claims to Palestinian land and Israeli settlement expansion. The complex discussion also illustrated the application of the Responsibility to Protect (R2P) Principle in the protection of Human Rights (HAM) as well as the international response to the conflict. Apart from examining political and historical aspects, this research highlights the impact of conflict on human existence. These conflicts not only raise questions about human rights and justice, but also have significant psychological and physical forces on the region's populations. This research highlights the complexity of the Israeli-Palestinian conflict which requires a deep understanding of many dimensions, including political, social and religious aspects. Joint efforts of the international community are necessary to find sustainable solutions, creating a safe and peaceful environment for all parties involved.